A metaphysics for the study of religion: A critical reading of Russell McCutcheon. (April 2020) - Schilbrack, Kevin
Russell McCutcheon is one of the foremost proponents of what he calls "the critical study of religion, " that is, the shift to reflect critically on the concepts used in the academic study of religion, who invented them, and why. The critical study of religion leads to the realization that the concepts with which we think were invented by particular people, at a particular historical location, for a particular purpose. What are the philosophical implications of this? McCutcheon defends a debunking or non-realist answer and contrasts this with my realist approach, and he is right to do so. This paper argues that those involved in the critical study of religion therefore face a choice between a non-realist and a realist metaphysics, that McCutcheon's arguments against realism fail, and that those who wish to offer any kind of materialist account in which religious social structures shape human agency and subjectivity should adopt a critical study of religion that is also realist.